Opportunities and limitations of introducing artificial intelligence technologies into reproductive medicine - V. A. Lebina; O. Kh. Shikhalakhova; A. A. Kokhan; I. Yu. Rashidov; K. A. Tazhev; A. V. Filippova; E. P. Myshinskaya; Yu. V. Symolkina; Yu. I. Ibuev; A. A. Mataeva; A. N. Sirotenko; T. T. Gabaraeva; et al. (Акушерство, гинекология и репродукция)
Given the increasing problem of infertility in the Russian Federation, assisted reproductive technologies (ART) have proven to be one of the most effective treatments for this condition. Notably, the introduction of ART methods, particularly in vitro fertilization (IVF), has led to markedly increased birth rates over the past two decades. Studies show that machine learning algorithms can process images of embryos to assess their quality, thus facilitating the selection of the most viable among them for transfer. There are ethical and technical barriers hindering the widespread adoption of artificial intelligence (AI) in clinical practice, including concerns over data privacy as well as a need to train specialists to deal with new technologies. AI can analyze vast amounts of data, including medical histories and research results, to more accurately predict pregnancy outcomes. This enables doctors to make more justified clinical decisions. In the future, AI algorithms will be able to analyze patient data more efficiently, helping to identify the causes of infertility at earlier stages.